Relation between high levels of myeloperoxidase in the culprit artery and microvascular obstruction, infarct size and reverse remodeling in ST-elevation myocardial infarction - Stamboul, Karim; Zeller, Marianne; Rochette, Luc; Cottin, Yves; Cochet, Alexandre; Leclercq, Thibault; Porot, Guillaume; Guenancia, Charles; Fichot, Marie; Maillot, Nicolas; Vergely, Catherine; Lorgis, Luc; et al. (PLOS ONE, 2017)
To better understand the role of myeloperoxidases (MPO) in microvascular obstruction (MO) phenomenon and infarct size (IS) using cardiac magnetic resonance (CMR) data in patients with acute myocardial infarction (AMI). 40 consecutive patients classified according to the median level of MPO in the culprit artery. A CMR study was performed during the week following AMI and at 6 months, with late gadolinium enhancement sequences. Persistent MO was observed in the same proportion (50 vs. 65%, p = 0.728) between the low vs. high MPO group levels. However, the extent of the microvascular obstruction was significantly greater in the high-MPO group (6 (0-9) vs.16.5 (0-31), p = 0.027), together with a greater infarct size, and a trend towards a lower left ventricular ejection fraction (LVEF) (p = 0.054) at one week. CMR data at 6 months showed that reverse systolic remodeling was two fold more present in the low-MPO group (p = 0.058). Interestingly, the extent of MO (8.5 (6.5-31) vs. 4.1 (3-11.55), p = 0.042) and IS remained significantly greater (24.5 (9.75-35) vs. 7.5 (2.5-18.75), p = 0.022) in the high-MPO group. Moreover, MPO in the culprit artery appeared to correlate positively with MPO in non-culprit arteries and serum, and with troponin levels and peak CK. This patient-based study revealed in patients after AMI that high MPO levels in the culprit artery were associated with more severe microvascular obstruction and greater IS. These findings may provide new insights pathophysiology explanation for the adverse prognostic impact of MO.